Conflito de direitos: o discurso religiosos e o projeto de lei da Câmara nº 122 de 2006 - perspectivas teológicas para o diálogo e ação pública na luta pela criminalização da homofobia - Senger, Daniela (2014)
PLC 122/2006 was a bill aimed at criminalizing acts of prejudice and discrimination motivated by gender, sex, sexual orientation, gender identity, age and human disability, amending Law No. 7.716, of January 5, 1989, which criminalizes bias motivated by race, color, ethnicity, religion or national origin. From theological perspectives, the dissertation presents the bill from its emergence in the House of Representatives in 2001, to the culmination of the attachment of PLC 122/2006 to PLS 236/2012 in 2013 (a Senate bill that intends to amend the Penal Code). In the first chapter, we have provided conceptual and statistical data on homophobia, listed government programs that seek to eradicate homophobia in Brazil and in the world, and offered a historical overview of PLC 122/2006. In the second chapter, we have elaborated a discursive survey on the position of religious groups that were contrary to PLC 122/2006, namely evangelicals and Roman Catholics. These voices countered PLC 122/2006 with arguments that revolved around a possible restriction of religious freedom if the bill were approved, which created a conflict of rights between the parties that fought for or against it. Next, the study has been illustrated with a brief survey about the official discourse and positions of other religious voices (specifically the Protestant) that have been debating the issue. In the third chapter, we have addressed the question on how this clash relates to the establishment of the Secular State and the construction of human rights, identifying a conflict of rights generated from the complaint that the intervention of religious voices in politics and in the implementation of public policy injures the concept of Secular State. In contrast, for the evangelicals, a group that explicitly stands in defense of a "Christian morality" and a normative family" of a country with a Christian majority, this rejection also injures democracy and the Brazilian Constitution of 1988, which ensures all the citizen religious freedom and expression. As a right granted by the constitution and a mission evoked by the Christian confession of faith that teaches to uphold life in its diversity above any law or dogma, other church voices, Christian public theologies and ecumenical entities are called to contribute to the debate and the struggle for the human rights of LGBT people. After all, we advocate the ongoing dialogue on the urgent need to criminalize homophobia in Brazil assuming that the work is hard, conflicted and even painful, but the silence that oppresses needs to be broken and reported daily by civil society, churches (in their diversity), public theologies and ecumenical bodies, and, not least, by the representatives of people in Congress for a human construction of human rights of LGBT people.